2020
DOI: 10.2147/cmar.s252295
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA NEAT1 Promotes the Proliferation, Migration, and Metastasis of Human Breast-Cancer Cells by Inhibiting miR-146b-5p Expression</p>

Abstract: Background: Breast cancer (BC) is the most commonly diagnosed cancer in women. Tumor recurrence and metastasis are the key causes of death in BC patients. Long noncoding RNA (lncRNA) is closely associated with BC progression. lncRNA nuclear-enriched abundant transcript (NEAT)1 has been reported to regulate the proliferation and mobility of several types of cancer cells. However, how lncRNA NEAT1 affects the proliferation and invasion of BC cells is not known. Methods: Quantitative real time-polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…It would also be interesting to test if STAT3 regulates the expression of NEAT1 in the context of immune regulation, and if miR-222-3p mediated regulation would be physiologically important in this context as well. A recent study has shown that NEAT1 promotes cell proliferation, migration and metastasis in breast cancer by inhibiting miR-146b-5p ( Li et al, 2020 ). Our study has identified miR-222-3p as a novel target of NEAT that has important functional role in regulating hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…It would also be interesting to test if STAT3 regulates the expression of NEAT1 in the context of immune regulation, and if miR-222-3p mediated regulation would be physiologically important in this context as well. A recent study has shown that NEAT1 promotes cell proliferation, migration and metastasis in breast cancer by inhibiting miR-146b-5p ( Li et al, 2020 ). Our study has identified miR-222-3p as a novel target of NEAT that has important functional role in regulating hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“… LncRNA Neat1 miR-34c miR-146b-5p miR-224-5p miR-382-3p The lncRNA Neat1 stabilized the mature caspase-1 to promote pyroptosis [ 78 ]. Neat1 promoted metastasis in human various cancers, by inhibiting miR-146b-5p [ 161 ] in breast cancers, targeting miR-224-5p in malignant melanoma [ 162 ], by mediating miR-382-3p in ovarian cancer [ 163 ]. lncRNA MALAT1 miR-22 miR-23c lncRNA MALAT1 promoted pyroptosis as the ceRNA to competitively bind miR-22, which led to the levels of NLRP3 was affected.…”
Section: Pyroptosis In Cancer Metastasismentioning
confidence: 99%
“…mRNA and miRNA expression levels were normalized to the internal reference genes GAPDH and U6, respectively. Quantification of mRNA and miRNA expression was performed by using the 2 - ΔΔ Cq method ( 28 ).…”
Section: Methodsmentioning
confidence: 99%